Comparison of different therapeutic approaches for pulmonary cryptococcosis in kidney transplant recipients: a 15-year retrospective analysis - Chen, Shuyang; Yu, Guoqing; Chen, Meiyan; You, Yanjing; Gu, Lei; Wang, Qing; Wang, Huijuan; Lai, Guoxiang; Yu, Zongyang; Wen, Wen (Frontiers in Medicine, 2023)
Introduction: Organ transplant recipients are at increased risk of developing pulmonary cryptococcosis (PC) due to weakened cell-mediated immunity caused by immunosuppressors. However, the nonspecific symptoms associated with PC can often lead to misdiagnosis and inappropriate treatment. Methods: We conducted a retrospective analysis of data from 23 kidney transplant recipients with PC between April 2006 to January 2021. Results: The median time from transplantation to the diagnosis of pathology-proven PC 4.09 years. 17 patients presented with respiratory symptoms, including a sputum-producing cough and dyspnea. Additionally, 3 patients also developed central nervous system (CNS) infections. Chest CT scans frequently revealed nodule-shaped lesions, which can mimic lung carcinoma. Serological tests did not demonstrate any specific changes. 9 patients received surgical resection as treatment. 14 patients were treated with antifungal medication only. No recurrence was observed in all 23 patients.Our study suggests that fever and sputum-producing cough are common symptoms of PC, and cryptococcal meningitis should not be excluded if corresponding symptoms occur. Fluconazole is a common and effective antifungal agent, while surgical therapy should be considered This is a provisional file, not the final typeset article for patients who do not respond well to antifungal therapy. Clinicians should be aware of these findings when evaluating transplant recipients with respiratory symptoms.